ESTIMATIONS CONCERNING THE INCREASING OF THE WHEAT PRODUCTION IN PRAHOVA COUNTY - Daniela DANA; Irina-Adriana CHIURCIU; Valentina VOICU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The analysis aims to discover what methods can be applied such that the average of winter wheat production per ha would grow. The main objective of this study was to establish the mineral nutrition status of winter wheat in relation with the soil and climatic conditions in the SC Agrotehnic PAULESTI experimental plots. In order to evaluate the mineral nutrition status of plant, the macronutrients have been carried out when the plant, Renan cultivar, reached 4-5 cm height. The obtained data have been interpreted in relation with the optimum ranges of mineral content in dry matter mentioned in the specialty literature. Also, on the basis of soil data, the mineral fertilisation and lime recommendations have been established.